Comparative study on the antimicrobial activity of partitioned fractions of the stem-bark of ceiba pentandra (bombacaceae) - S., Njinga N.; I., Sule M.; U., Pateh U.; S., Hassan H.; N., Ache R.; T., Abdullahi S.; A., Danja B. (Journal of Health and Allied Sciences NU, 2015)
Due to the emergence of more and more drug resistance bacteria and the reported antibacterial activity of Ceiba pentandra, the antimicrobial activity of the partitioned ethyl-acetate and n-butanol fractions of the stem-bark of this plant were carried out on the following clinical isolates: Staphylococcus aureus; Streptococcus pyrogenes; corynebacterium ulcereans; Escherichia coli; Salmonella typhi; Shigella dysenterea; Enterococcus aerogenes; Pseudomonas aeruginosa; klebsiella pneumonia and the fungi Trichophytom rubrum, Microsporum sp., Aspergillus fumigatus and Aspergillus niger. Agar diffusion and broth delusion methods were used in this study. The ethyl acetate fraction showed wide spectrum antibacteria activity (with zones of inhibition between 27mm and 37mm) while the n-butanol extract showed activity only against the gram negative bacteria (zones of inhibition between 20mm and 21mm). The MIC ranged from 0.65 to 2.5 mg/ml and 2.5 to 5 mg/ml and MBC ranged from 2.5 mg/ml and 5 – 10 mg/ml for the ethylacetate and n-butanol respectively. Both fractions showed no activity against the fungi used in this study. The preliminary phytochemistry of the ethyl acetate showed the presence of only flavonoid and this may explain the activity against all the bacteria. The n-butanol showed the presence of carbohydrates, saponins, tannins and cardiac glycoside and the absence of flavonoid and alkaloids. This study justifies the use of this plant in herbal medicine.
Keywords: antimicrobial; Ceiba pentandra; minimum inhibitory concentration; bacteria